基于双重双面法的弧齿锥齿轮轮齿接触分析（TCA）研究 - 耿龙龙; 邓效忠; 曹雪梅 (Jixie chuandong)
Tooth contact analysis（TCA）is solve the nonlinear equations according to the surface parameters of machining parameter selection of reference point for the initial valueTooth contact analysis（TCA）is calculated the surface to solve the nonlinear equations,finally the tooth contact trace and transmission error is got.While using duplex spread blade,it does not need to set the reference point,the initial value can’t be given,it is difficult to solve nonlinear equations for TCA of duplex spread blade.According to the particularity of duplex spread blade,a way to select the initial point is designed,TCA of duplex spread blade is completed,the tooth contact trace and transmission error are got,the tooth contact conditions is intuitively reflected,the problem that TCA does not apply to duplex spread blade is solved,the theoretical basis for practical production and processing is provided.